(External debts of some Arab countries and their economic effects during the period (1995-2016 - Soliman, Hanan Mohamed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2018)
The Arab countries' external indebtedness have exacerbated since the 1995 till 2016. This is attributed to the incorrect financing policies that countries have adopted in financing the development. In addition, these countries continued in consuming, investing indebtedness in an extremely higher degree than their production, savings and exports.In light of the early mentioned facts, the study aims to develop the external indebtedness volume in some Arab countries(Egypt, Jordan, Tunisia, Morocco and Lebanon),its reasons, economic impacts and the most important strategies adopted to manage the external indebtedness since the 1995. the study introduces its most important conclude findings and some recommendations that can curb the negative effects of the phenomena investigated in the study. the research problem dwells in defining the actual reasons behind the increase of the some Arab countries' external debts. Does this indebtedness help realize the desired development? The descriptive technique through pursuing the path of the external indebtedness in the some Arab countries. The study is based on this hypotheses, the difference of Arab indebtedness conditions from one country to another country, and the public budgets' deficit for some Arab countries which leads to the increase of the external indebtedness.
Keywords: external debt crisis; Arab countries; conditions of external indebtedness; economic effects